A Method to Fabricate Disconnected Silver Nanostructures in 3D - Vora, Kevin (MyJove Corporation, 2012)
The standard nanofabrication toolkit includes techniques primarily aimed at creating 2D patterns in dielectric media. Creating metal patterns on a submicron scale requires a combination of nanofabrication tools and several material processing steps. For example, steps to create planar metal structures using ultraviolet photolithography and electron-beam lithography can include sample exposure, sample development, metal deposition, and metal liftoff. To create 3D metal structures, the sequence is repeated multiple times. The complexity and difficulty of stacking and aligning multiple layers limits practical implementations of 3D metal structuring using standard nanofabrication tools. Femtosecond-laser direct-writing has emerged as a pre-eminent technique for 3D nanofabrication.(1,2) Femtosecond lasers are frequently used to create 3D patterns in polymers and glasses.(3-7) However, 3D metal direct-writing remains a challenge. Here, we describe a method to fabricate silver nanostructures embedded inside a polymer matrix using a femtosecond laser centered at 800 nm. The method enables the fabrication of patterns not feasible using other techniques, such as 3D arrays of disconnected silver voxels.(8) Disconnected 3D metal patterns are useful for metamaterials where unit cells are not in contact with each other,(9) such as coupled metal dot(10,11)or coupled metal rod(12,13) resonators. Potential applications include negative index metamaterials, invisibility cloaks, and perfect lenses. In femtosecond-laser direct-writing, the laser wavelength is chosen such that photons are not linearly absorbed in the target medium. When the laser pulse duration is compressed to the femtosecond time scale and the radiation is tightly focused inside the target, the extremely high intensity induces nonlinear absorption. Multiple photons are absorbed simultaneously to cause electronic transitions that lead to material modification within the focused region. Using this approach, one can form structures in the bulk of a material rather than on its surface. Most work on 3D direct metal writing has focused on creating self-supported metal structures.(14-16) The method described here yields sub-micrometer silver structures that do not need to be self-supported because they are embedded inside a matrix. A doped polymer matrix is prepared using a mixture of silver nitrate (AgNO(3)), polyvinylpyrrolidone (PVP) and water (H(2)O). Samples are then patterned by irradiation with an 11-MHz femtosecond laser producing 50-fs pulses. During irradiation, photoreduction of silver ions is induced through nonlinear absorption, creating an aggregate of silver nanoparticles in the focal region. Using this approach we create silver patterns embedded in a doped PVP matrix. Adding 3D translation of the sample extends the patterning to three dimensions.